Assisting Poultry Farming MSMEs in Formulating Halal and Affordable Feed to Increase Productivity - Kumala, Destiana; Al Farisi, Muhammad Salman; Haryadi, Rofiq Noorman; Usman , Usman; Ramdani, Akmal (Doctoral Program of Social Science, Pasundan University, 2025)
This community service program aims to strengthen the capacity of poultry farming MSMEs in formulating halal, affordable, and nutritionally balanced feed to improve livestock productivity. The assistance was carried out to address common challenges faced by small-scale farmers, including limited knowledge of halal feed standards, dependence on commercial feed with fluctuating prices, and the lack of skills in utilizing locally available raw materials. The program employed a participatory empowerment approach consisting of three main stages awareness and training, which introduced halal feed principles, identification of permissible ingredients, and cost-efficient formulation techniques technical workshops and hands-on practice, where participants collaboratively formulated and produced halal feed using locally sourced materials; and monitoring, which involved periodic supervision, evaluation of feed quality, and assessment of changes in farm productivity. The results of the program indicate a positive impact on the targeted MSMEs. Participants demonstrated an increased understanding of halal feed requirements and the ability to independently formulate balanced rations at lower cost. The application of the newly formulated feed contributed to improved growth rate, feed efficiency, and overall poultry performance. In addition, farmers reported reduced dependence on commercial feed and enhanced confidence in maintaining halal compliance. This program highlights the significance of capacity building and locally based feed innovation as strategic efforts to improve productivity and competitiveness among poultry farming MSMEs.